(3TQM GdbGfhf GdJLGQjs - (3eMeO ahRj(B, (3SGejs ((3YeGf(B:s (3ecJHI OGQ GdKbGaI ddfTQ hGdJhRjY(B,s, 2004)
(3fThA GdbGfhf GdJLGQj hJWhQg, GdCYeGd GdJLGQjI hJWhQgG, GdJGLQ hGdeJLQ, GdYbhO GdJLGQjI CMcGegG GdYGeI hJWhQgG(B.s
(3GdeQGLY U(B.321s
Keywords: (3GdCYeGd GdJLGQjIs; (3GdbGfhf GdJLGQjs